Multifamily housing construction in Russia: supply elasticity and competition. Issue 2 (3rd August 2016) - Polidi, Tatyana D.
ABSTRACT: Housing unaffordability and unavailability are major socio-economic problems in modern Russia, and result from market failure to provide a sufficient volume of new housing at reasonable prices. About 29% of new newly constructed housing units are self-build single-family houses produced outside the market. Professional builders are specialized mainly in constructing multifamily houses, generally in urban areas. This study analyses the efficiency of this market segment of housing construction, and shows that: (1) it is characterized by low price elasticity; (2) the responsiveness of new housing supply to demand changes is weak due to various supply restrictions and the imperfectly competitive behaviour of building companies and (3) self-built housing construction helps limit the market power of builders, which is stronger in more developed (and more profitable) regional markets and weaker in less developed ones.